Influence of Dose Rate on the Cellular Response to Low- and High-LET Radiations - Wozny, Anne-Sophie; Alphonse, Gersende; Battiston-Montagne, Priscillia; Simonet, Stéphanie; Poncet, Delphine; Testa, Etienne; Guy, Jean-Baptiste; Rancoule, Chloé; Magné, Nicolas; Beuve, Michael; Rodriguez-Lafrasse, Claire (Frontiers in Oncology, 2016)
Nowadays, head and neck squamous cell carcinoma (HNSCC) treatment failure is mostly explained by locoregional progression or intrinsic radioresistance. Radiotherapy (RT) has recently evolved with the emergence of heavy ion radiations or new fractionation schemes of photon therapy, which modify the dose rate of treatment delivery. The aim of the present study was then to evaluate the in vitro influence of a dose rate variation during conventional RT or carbon ion hadrontherapy treatment in order to improve the therapeutic care of patient. In this regard, two HNSCC cell lines were irradiated with photons or 72 MeV/n carbon ions at a dose rate of 0.5, 2, or 10 Gy/min. For both radiosensitive and radioresistant cells, the change in dose rate significantly affected cell survival in response to photon exposure. This variation of radiosensitivity was associated with the number of initial and residual DNA double-strand breaks (DSBs). By contrast, the dose rate change did not affect neither cell survival nor the residual DNA DSBs after carbon ion irradiation. As a result, the relative biological efficiency at 10% survival increased when the dose rate decreased. In conclusion, in the RT treatment of HNSCC, it is advised to remain very careful when modifying the classical schemes toward altered fractionation. At the opposite, as the dose rate does not seem to have any effects after carbon ion exposure, there is less need to adapt hadrontherapy treatment planning during active system irradiation.